Phytotoxic effects of trivalent chromium-enriched water irrigation in Vigna unguiculata seedling. (20th November 2018) - Chow, Y.N.; Lee, L.K.; Zakaria, N.A.; Foo, K.Y.
Abstract: The present study attempts to investigate the degree of inhibition of trivalent chromium on the seed germination and embryonic axis growth of Vigna unguiculata seedlings. The alteration of chloroplastic pigments, and the unique roles of different enzymatic and non-enzymatic antioxidants against chromium-induced stress were elucidated. Chromium treatment has adversely retarded the elongation of roots and shoots, with the inhibition rate of 68.5% and 70%, respectively. The chlorophyll- a, chlorophyll- b, and carotenoid contents were significantly altered, denoted the reduction of 60.3%, 67.2%, and 43.7%, respectively. Higher stimulation effects have been observed in the ascorbate peroxidase, catalase, and guaiacol peroxidase at different degrees, and a greater accumulation of proline was detected. The current findings provided an up-to-date picture on the phytotoxicity of chromium ions on the physical, chemical, and physiological alterations of Vigna unguiculata seedlings, and triggered the cellular enzymatic and non-enzymatic antioxidants against these oxidative injuries. The health threats associated with the excessive accumulation of anthropogenic pollutants in the food crops could be exacerbated on a wider scale by unregulated wastewater irrigation practice, and place an alarming deterioration to the sustainability of water-food nexus. Graphical abstract: Image Highlights: Highlight the impacts of chromium contaminated water irrigation on plants. Outline the physical and biochemical responses, and antioxidative defense system. Reveal the inhibition on embryonic axis growth and reduction in chlorophyll level. Indicate the significant enhancement in enzymatic and non-enzymatic reactions. Elucidate the mechanism of chromium-induced toxicity in water-soil-plant system.